2006
DOI: 10.1002/ffj.1577
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antituberculosis activity of the volatile oil ofHeliotropium indicum Linn. growing in Phitsanulok, Thailand

Abstract: The volatile oil from the aerial parts of H. indicum was isolated by hydrodistillation and analysed by a combination of gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS). The essential oil was obtained in 0.004% yield as a light brown liquid. The major constituents of the volatile oil of H. indicum were phytol (49.1%), 1-dodecanol (6.4%) and β β β β β-linalool (3.0%). In addition, the volatile oil showed significant antituberculosis activity against Mycobacterium tuberculosis H37Ra i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
0
18
1
1
Order By: Relevance
“…The main constituents were phenylacetaldehyde (22.2%), (E)-2-nonenal (8.3%), hexahydrofarnesylacetone (8.4%) and (E, Z)-2-nonadienal (6.1%). Except for the presence of linalool, borneol and tricosane, the present oil sample differed greatly from the literature report [11]. Phytol and 1-dodecanol, which constituted the bulk of the The chemical profile of each of the 49 constituents of the leaf and stem oils of B. pilosa revealed the abundance of sesquiterpene compounds ( Table 5).…”
contrasting
confidence: 78%
“…The main constituents were phenylacetaldehyde (22.2%), (E)-2-nonenal (8.3%), hexahydrofarnesylacetone (8.4%) and (E, Z)-2-nonadienal (6.1%). Except for the presence of linalool, borneol and tricosane, the present oil sample differed greatly from the literature report [11]. Phytol and 1-dodecanol, which constituted the bulk of the The chemical profile of each of the 49 constituents of the leaf and stem oils of B. pilosa revealed the abundance of sesquiterpene compounds ( Table 5).…”
contrasting
confidence: 78%
“…A comparison of essential oil constituents of H. indicum of this study with the compounds of plant growing in Thailand [19] was found to be completely different. Apart from this, the report from Nigeria grown H. indicum plant only three compounds viz., methyl salicylate (1.2%), (E)-β-ionone (1.9%) and eugenol (2.4%) [20] were found to be common compared to the present study.…”
Section: Resultsmentioning
confidence: 59%
“…The alkaloids viz., indicine [10], indicinine [15], helindicine, lycopsamine [16], pestalamide B, glycinamide,N-(1-oxooctadecyl) glycyl-Lalanylglycyl-L-histidyl [17] and indicine-N-oxide [18] have been isolated from H. indicum. The major volatile compounds phytol, 1-dodecanol, and β-linalool have been reported from Thailand and the oil showed significant anti-tuberculosis activity against Mycobacterium tuberculosis H37Ra in the Alamar blue assay system with a MIC of 20.8 μg/mL [19]. Another report from Nigeria reported phenylacetaldehyde, (E)-2-nonenal and (E,Z)-2-nonadienal and hexahydrofarnesylacetone [20] were the major constituents.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed significant antituberculosis activity with an MIC of 20.8 µg/ml 37 . The antifungal activity 38 of the aqueous extract of fresh leaves against Fusarium oxyparum and antibacterial activity 39 41 .…”
Section: Fig 2: Some Important Pyrrolizidine Alkaloids Of H Indicummentioning
confidence: 91%
“…In another experiment, the volatile oil isolated by hydrodistillation was analysed by a combination of GC-FID and GC-MS. The major constituents of the volatile oil were phytol (49.1%), 1-dodecanol (6.4%) and β-linalool (3.0%) 37 .…”
Section: Fig 1: Heliotropium Indicum Linnmentioning
confidence: 99%